The Impact of Motivation and Learning Strategies as Predictors of Biology Performance among Non- Science Majors - Nacionales, Erma N.; Muyong, Jr., Pelagio M.; Gavasan, Joann C. (Asia Pacific Higher Education Research Journal (APHERJ), 2016)
Science Education has improved the quality of life, developed competitiveness, and helped understand global issues. Thus, the present study identified the impact of motivation and learning strategies in Biology among non- science majors. The respondents chosen through simple random sampling for this study were the 83 Information Technology students taking Biology. The study used the descriptive method of research using Biology Motivation Questionnaire (Glynn and Koballa, 2005) and Motivated Strategies for Learning Questionnaire (Pintrich et al., 1991). These instruments were administered thrice: at the start of classes, and a week before the midterm and the final examinations. The data gathered were tabulated and analyzed. The student’s midterm exam scores in biology were used as measures of achievement. The statistical tools employed were mean, standard deviation, ANOVA and regression analysis. Results showed that non- Science majors have high motivation level. Among the sub- components: intrinsic, and extrinsic motivation, personal relevance and self- determination have very high contribution to the level of motivation especially to the high performers. The results further revealed that all the respondents have the low assessment anxiety in Biology. For the learning strategies used, high performers often used organization, metacognitive selfregulation skills, rehearsal and elaboration while low performers seldom used the given strategies. Average performers often used these strategies including critical thinking. The level of motivation is significantly different among the different course performers. Among the learning strategies, there is a significant difference in the use of organization, metacognitive self- regulation skills and rehearsal. Furthermore, the extrinsic and intrinsic motivation, personal relevance and self-determination are significant predictors of better performance in Biology. In conclusion, the level of motivation and learning strategies used can predict the level of Biology performance of non-science majors.